PARENTERAL IRON SUCROSE IN IRON DEFICIENCY ANAEMIA OF PAEDIATRIC CHRONIC KIDNEY DISEASE - Moorani, Khemchand N; Asim, Sadaf (Journal of Ayub Medical College Abbottabad, 2011)
Background: Erythropoietin (Epo) and iron therapy plays a major role in the management of renal anaemia. Iron sucrose (IS) has been used to treat iron deficiency anaemia (IDA) and to maintain adequate iron store in chronic kidney disease (CKD). The objective of the study was to determine the response and safety of IS in the treatment of IDA. Methods: This retrospective study was carried out in the Department of Nephrology, National Institute of Child Health, Karachi from Dec 2008 to Dec 2010. Children aged 6 months to 14 years, CKD-stage 2-5, and IDA were included. Pertinent data including age, gender, serum creatinine (SCr), CKD-stage, aetiology, treatment mode, IS dose, pre- and posttreatment parameters and side effects were collected and analysed. Results: Among 35, majority (66%) were boys. Mean age was 6.97±4.13 years and mean SCr was 3.78±3.1 mg/dl. Majority were in CKDstage 4-5 and treated conservatively. Major aetiologies were hypoplasia-dysplasia (40%), juvenile nephronophthiasis (17.14%), posterior urethral valves, and stones. Baseline mean Hb and Transferrin Saturation (TS) was 7.38±1.38 g/dl and 11.19±5.28% respectively. Mean Hb increased to 9.22±16.32 g/dl with correction of iron deficit (p<0.001) and a sustained rise in Hb was observed after Epo and maintenance iron sucrose. Mean TS% increased to 49.13±18% (p<0.001). No major side effects were observed except iron overload. Conclusion: Iron sucrose was effective in improving IDA in CKD without significant side effects. Iron sucrose may be used to treat IDA with monitoring for iron overload. Keywords: Iron deficiency, anaemia, iron sucrose, chronic kidney disease